2018
DOI: 10.1177/0954405417752513
|View full text |Cite
|
Sign up to set email alerts
|

Some investigations in grindability improvement of Inconel 718 under ecological grinding

Abstract: This work explores the improvement in grinding characteristics of Inconel 718 (IN718) using soluble oil under minimum quantity lubrication and liquid nitrogen (LN2) environments. The coolant flow rate in minimum quantity lubrication and LN2 grinding has been regulated through indigenously developed setups. Grinding performance has been studied in terms of on-machine measured grinding forces and centre line average surface roughness (Ra). The obtained grinding characteristics have been compared with the outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…From these, the most suitable cut-off length for our purposes (turning) was determined as 0.8 mm for Ra values of the machined workpieces. 34,35 While Ra measurements were carried out, measurements were taken from three different points for 5.6 mm from the surfaces of machined workpiece at 0.8 mm of cut-off length; and arithmetical mean of these measured values were calculated. In general, V B is referenced for tool wear measurement since the life of a cutting tool is assessed with real cutting time once V B value reaches at a limited value of 0.3 mm.…”
Section: Conventional Cooling Liquid and Mql Applicationmentioning
confidence: 99%
“…From these, the most suitable cut-off length for our purposes (turning) was determined as 0.8 mm for Ra values of the machined workpieces. 34,35 While Ra measurements were carried out, measurements were taken from three different points for 5.6 mm from the surfaces of machined workpiece at 0.8 mm of cut-off length; and arithmetical mean of these measured values were calculated. In general, V B is referenced for tool wear measurement since the life of a cutting tool is assessed with real cutting time once V B value reaches at a limited value of 0.3 mm.…”
Section: Conventional Cooling Liquid and Mql Applicationmentioning
confidence: 99%
“…Many solutions are proposed in order to reduce the amount of heat transferred to the surface of the part, such as using a appropriate cooling/lubrication regime [6,7]; special cooling methods, for example, minimum quantity lubrication (Minimum Quantity Lubricant -MQL) [8][9][10]; an open-structure grinding wheel for guiding the coolant from the inside of the spindle to the grinding zone through the gap between the abrasive grains [3]; the grinding with radial holes for guiding the coolant in the same way [3]. However, the fabrication of the open-structure grinding wheel is not applicable if the binder is ceramic and rubber, whereas these two types of binder are probably most common for producing grinding wheels, especially the ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, from this 30%, between 7 and 17% of the cost is caused by coolant systems 5 . Traditional coolant systems are based on water-miscible cutting fluids, and their high spatial volume requires large storage capacity and high-powered pumps, which further increase the grinding costs 6 . In addition to this impact on the bottom line, coolant systems have a harmful effect on the environment and pose health risks to the operator.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, Ra roughness and forces did not present significant differences in comparison with conventional grinding processes. Four years later, Sinha et al 6 compared the use of MQL and LN 2 environment to dry grinding of Inconel 718. They found that using MQL and LN 2 reduced cutting forces and promoted better grit-workpiece interaction.…”
Section: Introductionmentioning
confidence: 99%